Antiviral Mx proteins have an ancient origin and widespread distribution among eukaryotes - Caroline A. Langley; Peter A. Dietzen; Michael Emerman; Jeannette L. Tenthorey; Harmit S. Malik (Proceedings of the National Academy of Sciences, 2025)
Mx proteins, first identified in mammals, encode potent antiviral activity against a wide range of viruses. Mx proteins arose within the Dynamin superfamily of proteins (DSP), which mediate critical cellular processes, such as endocytosis and mitochondrial, plastid, and peroxisomal dynamics. Despite their crucial role, the evolutionary origins of Mx proteins are poorly understood. Through comprehensive phylogenomic analyses with progressively expanded taxonomic sampling, we demonstrate that Mx proteins predate the interferon signaling system in vertebrates. Our analyses find an ancient monophyletic DSP lineage in eukaryotes that groups vertebrate and invertebrate Mx proteins with fungal MxF proteins, the largely uncharacterized plant and algal Dynamin 4A/4C proteins, and representatives from several other eukaryotic lineages, suggesting that Mx-like proteins date back close to the origin of Eukarya. Our phylogenetic analyses also find host-encoded and nucleocytoplasmic large DNA viruses-encoded DSPs interspersed in four distinct DSP lineages, indicating recurrent viral theft of host DSPs. Our analyses thus reveal an ancient history of viral and antiviral functions encoded by the Dynamin superfamily in eukaryotes.